MANDATORY SUPERVISED INTERNSHIP IN THE BACHELOR’S COURSE IN AGRONOMY, A PARTNERSHIP BETWEEN UFRA CAMPUS OF CAPANEMA AND THE MUNICIPAL SECRETARIAT OF AGRICULTURE OF THE MUNICIPALITY OF PRIMAVERA – PA - Ono de Vasconcelos, Ariane; Marciele Melo da Silva, Vitória; Félix dos Santos, Raíssa; Fernanda Soares do Nascimento, Maria; José de Sousa da Silva, Bruno; Mayron Rodrigues Costa, Allan; Marcelo Santos da Costa, João; Pereira Siqueira, Cairo; Gabrielle Belo da Silva, Zara; Almeida Seabra Silva, Diocléa (Journal of Interdisciplinary Debates, 2024)
Supervised internship report aimed at technical visits and guidance to small producers in the municipality and activities on the environment developed in partnership with the Municipal Secretariat for the Environment and Sustainable Rural Development (SEMMA) and the Municipal Secretariat of Agriculture (SEMAGRI) . As well as, investigating locations in the municipality of Primavera in the State of Pará to carry out the practice of mechanization, carrying out environmental education in municipal and state schools, revitalizing public squares with ornamental plant seedlings, developing internal documentation with the Secretariat and, also, carry out technical visits to communities in the municipality that grow açaí.